2018
DOI: 10.1186/s12889-018-5368-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining the spatiotemporal evolution of vaccine refusal: nonmedical exemptions from vaccination in California, 2000–2013

Abstract: BackgroundVaccine hesitancy continues to be an issue throughout the United States, as numerous vaccine hesitant parents are choosing to exempt their children from school-entry vaccination requirements for nonmedical reasons, despite the safety and effectiveness of vaccines. We conduct an analysis of how vaccine refusal, measured by the use of nonmedical exemptions (based on personal or religious beliefs) from vaccination (NMEs), evolved across space and over time in California.MethodsUsing school-entry data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
0
13
0
4
Order By: Relevance
“…Third, our goal has been to identify a setting where PBE hotspots are especially likely to occur, but our theory does not explain PBE concentrations outside of homogeneous pockets (see non-bold cells in Tables 5 and 6). Additional theoretical and empirical work—such as Delamater and colleagues’ (2018) study of spatial spillover effects—is needed to understand other high-PBE settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, our goal has been to identify a setting where PBE hotspots are especially likely to occur, but our theory does not explain PBE concentrations outside of homogeneous pockets (see non-bold cells in Tables 5 and 6). Additional theoretical and empirical work—such as Delamater and colleagues’ (2018) study of spatial spillover effects—is needed to understand other high-PBE settings.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the state keeps accessible government records, including data on the percentage of elementary school students who receive vaccine exemptions and the educational attainment of students’ parents (a key predictor in our analysis). Third, in the years leading up to the measles outbreak, California had one of the highest PBE rates of all 50 states, with documented spatial clustering of PBEs (Carrel and Bitterman 2015; Delamater et al 2018). Fourth, due to its size, its large and varied economy, and its demographic diversity, there is a significant amount of variation in terms of the composition of communities in which schools are located.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed also in developed countries, such as the US, where a decrease in vaccination coverage was observed in children. This was mainly induced by a substantial increase in vaccine hesitancy among parents who chose to excuse their children from school-entry vaccination requirements for non-medical reasons (Delamater et al, 2018). A decrease in vaccination coverage was observed in US also for adult patients, as highlighted by a recent study that analyzed data from the 2015 National Health Interview Survey; it confirmed that, except for a moderate gain for some vaccines, coverage was low (Williams et al, 2017).…”
mentioning
confidence: 99%